2018
DOI: 10.3390/ijms19010161
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Different Types of Excitability in Large Somatosensory Neurons and Its Plastic Changes in Pathological Pain States

Abstract: Sensory neuron types have been distinguished by distinct morphological and transcriptional characteristics. Excitability is the most fundamental functional feature of neurons. Mathematical models described by Hodgkin have revealed three types of neuronal excitability based on the relationship between firing frequency and applied current intensity. However, whether natural sensory neurons display different functional characteristics in terms of excitability and whether this excitability type undergoes plastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…; Xie et al . ). Consequently, the optogenetics applied to the PNS would never be useful unless they could be selectively applied to a specific group of neurons.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Xie et al . ). Consequently, the optogenetics applied to the PNS would never be useful unless they could be selectively applied to a specific group of neurons.…”
Section: Introductionmentioning
confidence: 97%
“…Among them, a major difficulty is the heterogeneous nature of primary sensory neurons (dorsal root ganglion (DRG) neurons), which are composed of different classes of neurons, each of which has a distinct sensory modality such as nociception and proprioception (Hammond et al 2004;Fang et al 2005;Ruscheweyh et al 2007;Usoskin et al 2015;Li et al 2016;Xie et al 2018). Consequently, the optogenetics applied to the PNS would never be useful unless they could be selectively applied to a specific group of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…While outside the scope of this article, DRG neurons may be further classified based on other morphologic and biochemical features. 22,23 In autonomic ganglia, neurons vary in size from uniformly small ( Figure 3B) to uniformly large (Figure 5) to a mixture of sizes ( Figure 6) depending on the ganglion location and cellular function.…”
Section: Normal Microanatomic Structures Of the Pnsmentioning
confidence: 99%
“…At the same time, we further explained the potential presynaptic analgesic mechanism of CCR2 as an analgesic target. A large number of studies have shown that DRG neurons are divided into different types according to their markers and excitability [ 40 , 41 ]. Therefore, in which neuron subtype CCL2/CCR2 functions is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%